Inflation and Teachers Job Performance in Public Schools in Nigeria - Bartholomew Ojochenemi, Ukpoju; Victor, Cosmas; Isaac Araiyegbemi , Abayomi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
The effect of inflation on teachers' work performance in Nigerian public schools was covered in this essay. The study is a review that relies on secondary sources. Print and internet publications provided the secondary data. The study found that public school teachers' work performance has been adversely impacted by inflation. The study also demonstrated how teachers' standard of living has been impacted by inflation, which has resulted in them walking to school and paying more for educational materials that are essential to curriculum implementation. The study makes the following policy recommendations in light of this finding: the government ought to raise the pay and benefits of public school teachers. The cost of educational materials for instructors and pupils in public schools ought to be covered by the government. In order to facilitate the transportation of teachers and pupils to and from public schools, both public and private organisations should provide school buses.